Hubungan Dukungan Keluarga dan Pengetahuan dengan Ambulasi Dini pada Pasien Post Operasi Abdomen - Lisnawati Rahayu; Hilman Syarif; Cut Husna (Journal of Telenursing (JOTING), 2023)
The study's objective was to know the determinant of the early ambulation of post-abdominal surgery patients. The type of study was quantitative. It found that 171 treated post-abdominal surgery patients as samples of the Government Hospital in Pidie. To collect the data, the researcher used a questionnaire sheet to know the characteristics of patients, family support, and knowledge of the early ambulation of post-abdominal surgery patients. The analysis data were descriptive and inferential through Chi-square and binary regression logistics. It showed that family support of (p=0,000) and Knowledge of (p=0,001) related to the early ambulation of post-abdominal surgery patients. It found that regression logistics analysis showed knowledge of (p =0,009; OR: 3,694) the most dominant determinant associated with the early ambulation of post-abdominal surgery patients. The knowledge obtained by patients from nurses is closely related to the implementation of early ambulation in posr-abdominal surgery patients. Therefore, it should increase the patient’s knowledge, and family, especially about the early ambulation of post-abdominal surgery. Keywords : Determinants, the early ambulation, post-surgery, abdomen